A Theoretical Framework for a Virtual Diabetes Self-Management Community Intervention. (October 2014) - Vorderstrasse, Allison; Shaw, Ryan J.; Blascovich, Jim; Johnson, Constance M.
Due to its high prevalence, chronic nature, potential complications, and self-management challenges for patients, diabetes presents significant health education and support issues. We developed and pilot-tested a virtual community for adults with type 2 diabetes to promote self-management education and provide social support. Although digital-based programs such as virtual environments can address significant barriers to reaching patients (i.e., child care, transportation, location), they must be strongly grounded in a theoretical basis to be well-developed and effective. In this article, we discuss how we synthesized behavioral and virtual environment theoretical frameworks to guide the development of SLIDES (Second Life Impacts Diabetes Education and Support).